Apprenticeship rehabilitated in a postmodern world? - Nielsen, Klaus [Verfasser]; Tanggaard Pedersen, Lene [Verfasser] (My University, 2011)
"In this article, it will be argued that in a postmodern society, there is a growing interest in apprenticeship. In a postmodern society, one of the issues dominating work life today is the need to learn local and pragmatic kinds of knowledge due to specialized, rapidly changing, and flexible forms of production. The resurrected interest in apprenticeships that we are witnessing is not due to mere chance or personal contributions to the field; additionally, they are not only a reflection of educational fads. Rather, apprenticeship learning is in line with current postmodern conceptions of knowledge. The change in production involves a relocation of knowledge, the importance and recognition of exemplary forms of acquiring knowledge, the primacy of pragmatic knowledge, knowledge as socially distributed, and knowledge as flexible, changing." (Autorenreferat, BIBB-Doku)
Keywords: T 2.1 Bildungstheorien; T 4.1 Philosophie; T 1.2 Historische Berufsbildungsforschung; Berufsbildungstheorie; Wirtschaftspädagogik; Historische Entwicklung; Postindustrielle Gesellschaft; Wissensgesellschaft